2016
DOI: 10.1007/s10018-016-0158-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic impacts of Japan’s renewable energy sector and the feed-in tariff system: using an input–output table to analyze a next-generation energy system

Abstract: We construct an input-output table to analyze a next-generation energy system. Based on this table, we estimate the effect of using renewable energy on Japan's economic structure as well as the feed-in tariff's contribution to the cost structure. The results clearly show that, induced by demand, existing power generation options and the production of existing passenger vehicles would be reduced and replaced by electric vehicles (EVs), plug-in hybrid vehicles (PHVs), and the renewable energy sector. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…We developed an Input-Output Table for a Next Generation Energy System (IONGES) which incorporated renewable energy based on a table prepared by MIC (Nakano et al 2017). 3 The IONGES has two types of tables; one incorporates renewable energy sectors that existed in 2005 (2005 IONGES) and the other incorporates renewable energy sectors up to the composition ratio assumed for 2030 (2030 IONGES).…”
Section: Methodsmentioning
confidence: 99%
“…We developed an Input-Output Table for a Next Generation Energy System (IONGES) which incorporated renewable energy based on a table prepared by MIC (Nakano et al 2017). 3 The IONGES has two types of tables; one incorporates renewable energy sectors that existed in 2005 (2005 IONGES) and the other incorporates renewable energy sectors up to the composition ratio assumed for 2030 (2030 IONGES).…”
Section: Methodsmentioning
confidence: 99%
“…After its implementation, research on FIT, as income compensation for RE operators, has been conducted in China, and has focused on institutional design (Ye, Rodrigues, & Lin, 2017;Zhang, M. M. et al, 2016), environmental impact (Wei et al, 2019), and the investment-inducing effect on energy business (Liu, Li, & Zha, 2016). In Japan, the research on FIT has demonstrated their large impact on the energy economy (Nakano, Arai, & Washizu, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We present more discussions on this later in the paper. 10 In addition to these basic variables we have experimented with some additional variables related to renewable energy generation, most of which turned out to be statistically insignificant. We plan to analyze these dropped variables further in our future study.…”
Section: Estimating Community-specific Economic Impacts Of Renewable mentioning
confidence: 99%
“…We also note that Nakano, Arai and Washizu[10] use Japanese Input-Output tables to analyze renewable energy.…”
mentioning
confidence: 99%